How to responsibly scale innovations in fragile settings? - Nortje, Karen; Al-Zu’bi, Maha; Cordova, K. (Global Dispatches, 2024)
This episode of the Global Dispatches podcast is produced in partnership with the CGIAR Research Initiative on Fragility, Conflict, and Migration for a series that examines what works to improve the well-being of people in Fragile and Conflict Affected Settings. CGIAR is a global partnership that unites international organizations engaged in research about food security.